Evaluating phosphorus dynamics from renewable sources to meet crop demand and minimise environmental pollution in Malawi. - Mnthambala, Frank (Cranfield University, 2021)
Like nitrogen (N), phosphorus (P) is an essential plant nutrient. When soils are deficient in P, external P in the form of fertilisers must be applied to increase crop yields. Population growth and changes in dietary needs have resulted in increased demand for P fertiliser for food and feed production, exerting pressure on P reserves. The future availability of P fertilisers is uncertain as reports indicate that the high-grade P reserves will be depleted in the next 100 years. On the other hand, human activities like conventional tillage, continuous cropping, and burning crop residues have led to nutrient leaching, increased soil acidity, increased erosion, reduced organic matter and reduced water holding capacity, all of which have contributed to overall reduced soil productivity. Most Malawian soils have low P, and farmers apply P fertilisers to harvest enough food. The scarcity of P will lead to an increase in fertiliser prices which will in turn, affect food security in Malawi. However, research has shown that organic materials like faecal sludge, organic waste and livestock manure could be used as alternative sources of P in agriculture. In some highly industrialized countries, P flow charts were developed to identify and quantify the organic P sources for recycling and management. However, until now, there has been no complete P flow analysis in any African country. Furthermore, organic fertilisers that have been tested have only been applied to crops based on N, not P, which may not affect soil health the same way. In addition, it is unclear if P mineralising from the organic fertilisers can maintain the available P concentration in the soil and result in the same crop yield as inorganic fertilisers Against this background, this project aimed at conducting a P flow analysis (PFA) using STAN Software to characterise and quantify P sources, flows, and sinks to determine options for waste minimisation, recovery, and inorganic fertiliser use reduction in Malawi. After the organic sources were identified, field experiments were implemented to evaluate the effects of organic P sources derived from organic market waste and faecal sludge on soil health in Malawi. Furthermore, the field experiments were used to study P mineralisation and availability from the P-based organic fertilisers during the plant growth period. The PFA results highlighted that there are 35000 Mg of recyclable organic P available annually, which is over two times Malawi’s annual P fertiliser demand (14000 Mg). The total amount of P applied to the soil for crop production per year is 21000 Mg of which 5300 is applied through animal manure, 1700 Mg through the decomposing mulch and faecal sludge, and the rest through inorganic fertilisers. Although 21000 Mg was applied, 25000 Mg left the soil through crop removal (23000 Mg) and soil erosion (2000 Mg), which resulted in a negative P balance of 1 kg P per hectare. Almost 5000 Mg of P in crop products goes to waste materials during postharvest handling processes, and 1100 Mg is exported in agricultural products. At the consumption level, 100 Mg of P is in food waste and 10000 Mg of P is consumed by the people. Out of the P consumed by people, 91% ended up in pit latrines, and the remaining 9% went to open defecation, WWTPs, and septic tanks. There is also 13000 Mg of P in manure and 4000 Mg in organic waste dumped in unofficial dumpsites, and 500 Mg P in landfills. Although there is organic P in faecal sludge, manure, and organic waste, only 16% of the organic P is recycled for agriculture. Inorganic P fertiliser represents 66% of the P fertiliser used for crop production. Manure is the most recycled organic P source (38% recycled), followed by organic solid waste (6%) and crop residues (5%). Annually, 9000 Mg of P is transferred to faecal matter, but none is recycled. In crop trials, the application of the organic P based fertilisers increased soil organic matter by 60% in two seasons at one field site (Bvumbwe) and 82% at the second (Makoka). Soil pH, which affects plant nutrient availability and microbial activities in the soil, increased from 4.75 to 5.82 in two seasons. There were almost six times more earthworms in the soil at Bvumbwe and four times more earthworms at Makoka compared to inorganically fertilised soil. Bulk density decreased only at Bvumbwe, and maize yield was not affected by P sources. The results on P mineralisation showed that available P in the soil from three weeks after planting to nine weeks increase the maize yield. Modelled results indicated that available P in the soil at three weeks accounted for 50%, at six weeks accounted 49%, and nine weeks after counted for 46% of the maize grain yield. At Makoka, at three and six weeks after planting in both seasons, available soil P was the same regardless of P source, but at nine weeks, the NPK treatment had lower available P. At Bvumbwe, in the first season, available P was the same at 3 and 9 weeks after planting but lower in NPK, NPK+MW and NPK+FSMW at six weeks. There was the same available P concentration in all treatments in the second season. In general, the organic P sources maintained available soil P at 25 mg/kg on average, above the threshold available P value for Malawi (18 mg/kg). At both sites, during the first season, PUE was the same. Only NPK and MW at 15 application rates had higher PUE in the second season. A comparison of PUE between the two sites showed that Bvumbe had a higher PUE than Makoka in both seasons. These findings indicate that Malawi can reduce its dependence on imported inorganic P by using organic sources that will supply P for crop growth and production just as well as the NPK fertiliser while improving soil health and reducing P losses to the environment
Keywords: phosphorus flow analysis (PFA); phosphorus sources; phosphorus flows; phosphorus sinks; phosphorus mineralisation; organic